2020
DOI: 10.1128/aem.02350-19
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Characterization of Lignocellulolytic Enzymes Secreted by the Insect-Associated Fungus Daldinia decipiens oita, Isolated from a Forest in Northern Japan

Abstract: Wood-devastating insects utilize their symbiotic microbes with lignocellulose-degrading abilities to extract energy from recalcitrant woods. It is well known that free-living lignocellulose-degrading fungi secrete various carbohydrate-active enzymes (CAZymes) to degrade plant cell wall components, mainly cellulose, hemicellulose, and lignin. However, CAZymes from insect-symbiotic fungi have not been well documented except for a few examples. In this study, an insect-associated fungus, Daldinia decipiens oita, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 48 publications
2
6
0
Order By: Relevance
“…These promoters are induced particularly in the presence of soluble oligosaccharides produced from xylan and cellulose. Similar results of the inducible promoter were reported in the case of the well-known fungus Daldinia decipiens oita and T. reesei when grown on different carbon sources ( Novy et al, 2019 ; Hori et al, 2020 ). Surprisingly, the genomic analysis showed that Daldinia decipiens oita lacks the lignin-degrading enzymes ( Hori et al, 2020 ).…”
Section: Resultssupporting
confidence: 82%
“…These promoters are induced particularly in the presence of soluble oligosaccharides produced from xylan and cellulose. Similar results of the inducible promoter were reported in the case of the well-known fungus Daldinia decipiens oita and T. reesei when grown on different carbon sources ( Novy et al, 2019 ; Hori et al, 2020 ). Surprisingly, the genomic analysis showed that Daldinia decipiens oita lacks the lignin-degrading enzymes ( Hori et al, 2020 ).…”
Section: Resultssupporting
confidence: 82%
“…The sample preparation and proteomic analysis were performed by following the previous study [54]. Briefly, 10 ÎŒg equivalent of the wheat germ cell-free extract (WEPRO7240H Lot: 15AQ02, CellFree Sciences) was precipitated by 20% (vol/vol) trichloroacetate (Wako Pure Chemical Corporation), and incubated for 20 min on ice, followed by ice-cold acetone wash for two times.…”
Section: Proteomic Analysis Of the Wheat Germ Cell-free Extractmentioning
confidence: 99%
“…S2), which lets cells grow and secrete a basal level of CAZymes that could subsequently hydrolyze LBG, including b-mannanase (GH5; SACTE_2347) (8,13). Alternatively, in a natural symbiont environment, a series of oligosaccharides such as mannooligosaccharides would be provided by symbiont microbes that can decompose plant cell wall components (27). When cells are exposed to mannose or mannobiose, they are imported into the cell by a putative mannose transporter (SACTE_5236, SACTE_5237, and SACTE_5238) (28), and this displaces SsManR from the 4 promoter regions (Prom_0383, Prom_0504, Prom_5235, and Prom_6282).…”
Section: Discussionmentioning
confidence: 99%